KEANEKARAGAMAN JENIS BURUNG DIURNAL PADA KAWASAN HUTAN LINDUNG DI DESA DANGE AJI KECAMATAN AIR BESAR KABUPATEN LANDAK - Prayogo, Hari; Panjaitan, Jeremy Natanael; Erianto, Erianto (JURNAL HUTAN LESTARI, 2024)
Birds are wild animals that can be found in almost all places on earth, including in the Dange Aji protected forest. The diversity of bird species in this location is not known with certainty, therefore it is important to carry out research on diurnal bird species in this location in order to obtain data regarding the diversity of diurnal bird species for bird conservation management efforts. The aim of this research is to examine the diversity of diurnal bird species in each land cover in the Protected Forest area in Dange Aji Village. This research was conducted using a survey method with data collection techniques using the point count method combined with line transects.The counting points were made at 6 (six) points in each land cover with a distance between points of 200 m. The data is analyzed and then used to calculate indices of dominance, diversity, similarity, richness and evenness. This research was conducted from July to August 2023. The results of observations carried out in Primary Forest, obtained a diversity index value of H'= 3,12, Agriculture and Shrubs H'= 2,72, Shrubs H'= 1,53 and Forest Secondary H'= 2,80. The diurnal bird species diversity index value in the Protected Forest in Dange Aji Village is H'= 3,30. Species diversity in each land cover is influenced by differences in different vegetation conditions, availability of feed and land cover.